On the new quantifiers and their use in multicriteria decision functions via ordered weighted aggregations - Chandramohan, Aarthi; Rao, M. V. C. (2006)
The goal of this paper is to present new and different quantifiers for ordered weighted aggregation and illustrate their applicability by a real-life example. The role of these operators in the formulation of multicriteria decision making functions, using the concept of quantifier guided aggregation, is also discussed.